Forgotten Cultural Heritage – the Church of Our Lady of Health in Gornja Brela (Archaeologia Adriatica, 2022)
The Church of Our Lady of Health was built at the beginning of the 18th century, and was in use until 1939, when services ceased to be held there. It is a relatively small single-nave building with a rectangular floor plan, without an apse and arched by a masonry barrel vault. Despite having been declared an immovable cultural heritage asset, due to its dilapidated condition, neglect and the possibility of complete collapse the church urgently needed conservation and restoration. For this reason, a restoration project has been launched and is being carried out by researchers from the Department of Archaeology and the Department of Art History of the University of Zadar in cooperation with the Brolanenses Association, the Public Institution Biokovo Nature Park and the Municipality of Brela. By using a different range of interdisciplinary methods, the work reconstructs a complex research process of valorisation and revitalisation of cultural heritage: from the moment of the construction of the church, studying the historical circumstances in which its cultural heritage exists and ultimately decays, to the creation of a statics study and a proposal for the restoration of the building, whose monumental value, regardless of its “modest” architecture and non-canonical historical and artistic distinctiveness, was confirmed by its permanent protection by the Ministry of Culture and Media of the Republic of Croatia.
Keywords: immovable cultural heritage; protection; revitalisation; cultural landscape; buffer zone